Translating an Imagetext: Verbal and Visual Self-Representation in Brett Whiteley’s Interior, Lavender Bay (1976) - Zanoletti, Margherita (TTR)

(untitled) (Association canadienne de traductologie, 2013)
This paper explores the relationship between the words and images in the drawing Interior, Lavender Bay by the Australian artist Brett Whiteley (1939-1992). This artwork combines the depiction of the artist’s home with a written element composed of the title, date, artist’s monogram, and a brief inscription. By examining Whiteley’s use of words and images in this drawing, the verbal/visual synergy that underpins his language is emphasized as a key aspect of his communicative appeal. The interpretive lens used in order to analyze Interior, Lavender Bay is interlingual translation. Translating Whiteley’s words from English into Italian allows not only to decipher the literal meaning and comprehend the symbolic function of his words, but also to highlight the relation between art and language. From this perspective, drawing on W. J. T. Mitchell’s Picture Theory (1994), the paper aims to discuss the functioning of images and the way in which interlingual translation might bring out latent connections in the source, opening a window on the interdisciplinary encounter between creative processes in the visual art and translation theory and practice.